High metabolic zinc demand within native Amundsen and Ross sea phytoplankton communities determined by stable isotope uptake rate measurements - R. M. Kell; R. M. Kell; R. M. Kell; R. J. Chmiel; D. Rao; D. M. Moran; M. R. McIlvin; T. J. Horner; N. L. Schanke; I. Sugiyama; R. B. Dunbar; G. R. DiTullio; et al. (Biogeosciences)
Zinc (Zn) is an essential micronutrient for most eukaryotic phytoplankton. Zn uptake by phytoplankton within the euphotic zone results in nutrient-like dissolved Zn (dZn) profiles with a large dynamic range. The combination of key biochemical uses for Zn and large vertical gradients in dZn implies the potential for rapid rates of Zn removal from the surface ocean. However, due to the ease of contamination at sea, direct measurements of dZn uptake within natural environments have not been previously made. To investigate the demand for dZn and for dissolved cadmium (dCd; a closely related nutrient-like element) within Southern Ocean phytoplankton communities, we conducted 67Zn and 110Cd tracer uptake experiments within the Amundsen Sea, Ross Sea, and Terra Nova Bay of the Southern Ocean. We observed a high magnitude of Zn uptake (ρZn > 100 pmol dZn L−1 d−1) into the particulate phase that was consistent with ambient depleted dZn surface concentrations. High biomass and low partial pressure of carbon dioxide in seawater (seawater pCO2) appeared to contribute to ρZn, which also led to increases in ρCd likely through the upregulation of shared transport systems. These high ρZn measurements further imply that only short timescales are needed to deplete the large winter dZn inventory down to the observed surface levels in this important carbon-capturing region. Overall, the high magnitude of Zn uptake into the particulate fraction suggests that even in the Zn-rich waters of the Southern Ocean, high Zn uptake rates can lead to Zn depletion and potential Zn scarcity.